2016
DOI: 10.1080/03007995.2016.1238352
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal tetracaine and oxymetazoline: a newly approved drug formulation that provides maxillary dental anesthesia without needles

Abstract: Intranasal 3% tetracaine plus 0.05% oxymetazoline provides sufficient dental anesthesia to complete restorative dentistry procedures in maxillary premolar, canine and incisor teeth. Future phase 4 clinical trials will evaluate whether this drug provides the necessary anesthetic profundity to perform more complex dental procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 17 publications
0
11
0
6
Order By: Relevance
“…A more objective way to determine pulpal anesthesia is with an electric pulp tester (19,20). Recent reviews of Kovanaze ® (39,41) have concluded that more studies will be needed to determine anesthetic success during "more invasive" dental procedures such as endodontic therapy. With the current study's use of an electric pulp tester, we have answered their call for an investigation of the efficacy of Kovanaze ® for maxillary pulpal anesthesia.…”
Section: Chapter 4: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A more objective way to determine pulpal anesthesia is with an electric pulp tester (19,20). Recent reviews of Kovanaze ® (39,41) have concluded that more studies will be needed to determine anesthetic success during "more invasive" dental procedures such as endodontic therapy. With the current study's use of an electric pulp tester, we have answered their call for an investigation of the efficacy of Kovanaze ® for maxillary pulpal anesthesia.…”
Section: Chapter 4: Discussionmentioning
confidence: 99%
“…Upon reaching the inferior and middle meati of the nose, Kovanaze ® bathes the anterior wall and floor of the maxillary sinus, penetrates the Schneiderian membrane and/or bony cortex there, and anesthetizes the anterior and middle superior alveolar (ASA and MSA) nerves before they reach the anterior and premolar tooth apices. Several authors have documented the variable course and presence of the superior alveolar nerves in the maxillary sinus (41)(42)(43)(44)(45). The superior alveolar nerves branch from the infraorbital nerve and usually travel within bony canals along the roof, anterior, posterior, and lateral walls of the maxillary sinus, but occasionally travel just below the Schneiderian membrane, before forming the superior dental plexus housed within the maxillary bone (43,45).…”
Section: Chapter 4: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…31 Kovanaze es el primer y único compuesto de aplicación intranasal usado para generar anestesia dental maxilar, el cual contiene una combinación de tetracaína (anestésico local) y oximetazolina (vasoconstrictor), compuestos que han sido usados durante varios años en medicina. 1,6,32,34 Esta técnica fue un hallazgo casual por parte del Dr. Mark Kollar, mientras realizaba la atención rutinaria en pacientes del área de Otorrinolaringología, a quienes colocaba una pulverización de oximetazolina para proporcionar hemostasia y seguido tetracaína en gel para controlar el dolor. Se manifestaron reportes anecdóticos de los pacientes de sensación diferente o de "entumecimiento" en los dientes anterosuperiores 1, .…”
Section: Anestesia Dental Intranasalunclassified
“…34 Desde entonces, diversos estudios se realizaron con el fin de evaluar la seguridad y eficacia de los compuestos para conseguir anestesia dental, considerando adecuada la concentración de la tetracaína al 3 % con oximetazolina al 0.5 % 34 . El clorhidrato de tetracaína es un anestésico local de tipo éster con alta potencia y efecto de larga duración, es degradado por estereasas plasmáticas, convirtiéndose rápidamente en un metabolito, el ácido p-butil aminobenzoico (PBBA), el cual es detectable fácilmente en el plasma sanguíneo 29, 32,35 . La oximetazolina es un agonista adrenérgico α1 y 2, su actividad simpaticomimética estimula los receptores adrenérgicos produciendo vasoconstricción, reducción del flujo sanguíneo y además ayuda a ralentizar la absorción sistémica de la tetracaína y prolongar sus concentraciones en el tejido 29,35 .…”
Section: Anestesia Dental Intranasalunclassified